The causal effects of baldrige excellence framework and lean in the Malaysian electrical and electronics manufacturing industry - Oon, Fok Yew (2021)
The aim of this research is to construct a comprehensive performance measurement model using the 2019-2020 Baldrige excellence framework criteria that examines the Malaysian Electrical and Electronics (E&E) industry. The criteria in this framework are leadership, strategy, customers, measurement, analysis and knowledge management (MAKM), workforce, operations and results. The previous study in the context of Business Excellence (BE) was focused more on aspects of quality management, organisational context, company performance but it often excluded the deployment of continuous improvement tools. Based on the research gaps, this research would like to assert the potency of the leadership of Baldrige setting as a driver that contributes positively to the Lean practice and BE elements of the company. The present study also integrating the Lean practices with Baldrige excellence framework to predict operations and the results of company performance. This integration may bridge the literature gap whereby the past studies have been conducted Lean, BE and operational performance individually. BE outcomes were achieved in both financial and non-financial performance metrics and the BE Models, Leadership theory and Lean model also guided the theoretical framework. The study also employed stratified random sampling from four sub-sectors of the E&E industry. A total of 156 respondents responded to the survey questionnaire from 488 companies that were sampled. This equates to a 32.0% response rate. The collected data were analysed using SPSS 23.0 and SmartPLS 3.3.2. The analysis found significant and positive relationships between strategy, operations and Lean practices on the achievement of BE. The results of this study promoted a better understanding of the BE in the E&E industry and its implications for activities concerning Lean practices, thus contributing to a wider body of knowledge. The survey instrument which combining Lean and BE was validated in this research can be reused in the other manufacturing sector studies on the initiatives deployment to predict business performance. Therefore, it contributes to the methodology perspective. The findings v of the research can become a reference, which can help the company focus on the right things in promoting excellence in their organisation and then pursuing BE Awards. Practical adoption of leadership and Lean practices may improve infrastructural decision areas of manufacturing strategy and the outcomes of this study may also be beneficial to policy makers of the Malaysian government and agencies such as Malaysia Productivity Corporation (MPC) and Ministry of International Trade and Industry (MITI). The scope of this study was limited because it was restricted to the Malaysia’s E&E industry only. As a suggestion, future research could be conducted by involving other industries.